2015
DOI: 10.1021/ja512637k
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Hydroformylation by a Rh-Catalyst Entrapped in a Supramolecular Metallocage

Abstract: Regio- and enantioselective hydroformylation of styrenes is attained upon embedding a chiral Rh complex in a nonchiral supramolecular cage formed from coordination-driven self-assembly of macrocyclic dipalladium complexes and tetracarboxylate zinc porphyrins. The resulting supramolecular catalyst converts styrene derivatives into aldehyde products with much higher chiral induction in comparison to the nonencapsulated Rh catalyst. Spectroscopic analysis shows that encapsulation does not change the electronic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
134
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(149 citation statements)
references
References 43 publications
3
134
1
11
Order By: Relevance
“…Es bilden sich dann unterscheidbare Koordinationsumgebungen im Käfig, und die Gesamtsymmetrie sinkt (Abbildung 3) 6. Komplementär dazu wurden heterometallische Käfige entwickelt, die aus mehreren Ligandentypen mit gut definierten Koordinationsumgebungen bestehen 7…”
Section: Variationsreichunclassified
See 1 more Smart Citation
“…Es bilden sich dann unterscheidbare Koordinationsumgebungen im Käfig, und die Gesamtsymmetrie sinkt (Abbildung 3) 6. Komplementär dazu wurden heterometallische Käfige entwickelt, die aus mehreren Ligandentypen mit gut definierten Koordinationsumgebungen bestehen 7…”
Section: Variationsreichunclassified
“…Die fortschreitende Funktionalisierung von Koordinationskäfigen hat bereits selektive Rezeptoren, chemische Transportsysteme und Reagenzien hervorgebracht, um reaktive Verbindungen zu stabilisieren und Giftstoffe zu maskieren. Die vielleicht spannendste Entwicklung ist die Synthese von nanometergroßen Reaktionsräumen, quasi künstliche Analoga zu Enzymen — auch wenn der Weg zur Kopie der Natur noch weit ist 7,16…”
Section: Photoschalterunclassified
“…[5,6] In such adynamic system, the resolution into one of the diastereomers is dependent on transfer of chiral information from as tereoregulating unit. [25,26] Theg roup of Reek demonstrated that stereocontrol in asupramolecular catalyst system could be achieved by either entrapment of the rhodium center in asupramolecular metallocage [27] or by molecular recognition of ac hiral cofactor in ab identate ligand. [12][13][14][15][16] Recently,control of axial chirality in a tropos ligand was demonstrated by association of small chiral molecules through hydrogen bonding.…”
mentioning
confidence: 99%
“…[24] Theg roups of Raynal and Vidal-Ferran achieved stereocontrol through the coassembly of chiral benzene-1,3,5-tricarboxamides (BTA) with achiral BTAs functionalized with P-donor moieties in ahelical scaffold. [25,26] Theg roup of Reek demonstrated that stereocontrol in asupramolecular catalyst system could be achieved by either entrapment of the rhodium center in asupramolecular metallocage [27] or by molecular recognition of ac hiral cofactor in ab identate ligand. [9,28] Also chiral phosphoric acids have been used for supramolecular stereoregulation through ion pairing in asymmetric catalysis.…”
mentioning
confidence: 99%
“…[2] In artifiziellen Systemen ist die Produktinhibierung eine große Hürde.D ennoch wurde eine Reihe von Reaktionen, wie Hydroformylierungen, [3] Hydrolysen, [4] Hydratisierungen, [5] Hydroalkoxylierungen, [6] Aza-Cope-Umlagerungen, [7] Diels-Alder-Reaktionen, Nazarov- [8] und Prins-Cyclisierungen, [9] Isomerisierungen [10] und Te rpen-Cyclisierungen, [11] katalysiert. Aufgrund von Kation-p-Wechselwirkungen wird die reaktive Iminiumspezies im Wirt eingeschlossen und reagiert in dieser begrenzten Umgebung.Die gebildeten Produkte unterscheiden sich um bis zu 92 %eev on den Kontrollversuchen ohne zugegebenen Wirt.…”
unclassified